2012
DOI: 10.1155/2012/560531
|View full text |Cite
|
Sign up to set email alerts
|

Traveling Wave Solutions of the Nonlinear (3 + 1)‐Dimensional Kadomtsev‐Petviashvili Equation Using the Two Variables (G/G, 1/G)‐Expansion Method

Abstract: The two variables -expansion method is proposed in this paper to construct new exact traveling wave solutions with parameters of the nonlinear -dimensional Kadomtsev-Petviashvili equation. This method can be considered as an extension of the basic -expansion method obtained recently by Wang et al. When the parameters are replaced by special values, the well-known solitary wave solutions and the trigonometric periodic solutions of this equation were rediscovered from the traveling waves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 32 publications
2
15
1
Order By: Relevance
“…As a pioneer work Li et al [15] has applied the two-variable (G ′ /G, 1/G)-expansion method and found the exact solutions of Zakharov equations. Some applications of the (G ′ /G, 1/G)-expansion method can be seen in [16,17,18,19,20]. (1/G ′ )-expansion method introduced by Yokus [21] firstly.…”
Section: Introductionmentioning
confidence: 99%
“…As a pioneer work Li et al [15] has applied the two-variable (G ′ /G, 1/G)-expansion method and found the exact solutions of Zakharov equations. Some applications of the (G ′ /G, 1/G)-expansion method can be seen in [16,17,18,19,20]. (1/G ′ )-expansion method introduced by Yokus [21] firstly.…”
Section: Introductionmentioning
confidence: 99%
“…As a pioneer work, twovariable (G ′ /G, 1/G)-expansion method was explained and applied to Zakharov equation in [22]. There are several studies related to this generalized method to obtain the traveling wave solutions of the some nonlinear differential equations [10,20,[23][24][25][26]. Hence it would be interesting to obtain the different forms of the traveling wave solutions of the Schamel-KdV equation.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear wave phenomena appear in various scientific and engineering fields, such as fluid mechanics, plasma physics, optical fibers, biology, solid state physics, chemical kinematics, chemical physics, and geochemistry. To obtain traveling wave solutions, many powerful methods have been presented, such as the inverse scattering method [1], the tanh-function method [2][3][4][5][6][7][8], the Hirota bilinear transform method [9], the truncated Painleve expansion method [10][11][12][13], the Backlund transform method [14,15], the Exp-function method [16][17][18][19][20], the Jacobi elliptic function expansion method [21][22][23], the generalized Riccati equations method [24][25][26], the ( / )expansion method [27][28][29][30][31][32][33], and the ( / , 1/ )-expansion method [34][35][36]. Conte and Musette [37] presented an indirect method to seek more solitary wave solutions of some NPDEs that can be expressed as polynomials in two elementary functions which satisfy a projective Riccati equation [38].…”
Section: Introductionmentioning
confidence: 99%